2021
DOI: 10.1038/s41467-021-23734-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of cellular forces using optical interference

Abstract: Important dynamic processes in mechanobiology remain elusive due to a lack of tools to image the small cellular forces at play with sufficient speed and throughput. Here, we introduce a fast, interference-based force imaging method that uses the illumination of an elastic deformable microcavity with two rapidly alternating wavelengths to map forces. We show real-time acquisition and processing of data, obtain images of mechanical activity while scanning across a cell culture, and investigate sub-second fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Cancer-cell protrusions exhibit dynamics on a range of time scales from seconds to minutes, as protrusion extension and migration movement involve fast-acting cytoskeletal polymerization. , Therefore, we monitored the force dynamics of the protrusions at an imaging time resolution on the order of seconds to minutes (Figure ), which has previously been done only in 2D cultures or microcavities . At Δt = 1 min imaging intervals, the cancer cells were found to generate forces in two phases that consist of resting phases punctuated by bursts of force exertion (Figure a).…”
Section: Individual Sub-nanonewton-scale Forces By Cancer-cell Protru...mentioning
confidence: 61%
See 1 more Smart Citation
“…Cancer-cell protrusions exhibit dynamics on a range of time scales from seconds to minutes, as protrusion extension and migration movement involve fast-acting cytoskeletal polymerization. , Therefore, we monitored the force dynamics of the protrusions at an imaging time resolution on the order of seconds to minutes (Figure ), which has previously been done only in 2D cultures or microcavities . At Δt = 1 min imaging intervals, the cancer cells were found to generate forces in two phases that consist of resting phases punctuated by bursts of force exertion (Figure a).…”
Section: Individual Sub-nanonewton-scale Forces By Cancer-cell Protru...mentioning
confidence: 61%
“…24,66 Therefore, we monitored the force dynamics of the protrusions at an imaging time resolution on the order of seconds to minutes (Figure 4), which has previously been done only in 2D cultures 31 or microcavities. 67 At Δt = 1 min imaging intervals, the cancer cells were found to generate forces in two phases that consist of resting phases punctuated by bursts of force exertion (Figure 4a). The results indicate that individual forces by a protrusion are dynamically exerted at the sub-nanoNewton scale over intervals lasting ≥60 s (Figures 4b−c), and the resting phase can take up to 6 min (Table S9).…”
Section: ■ Individual Sub-nanonewton-scale Forces By Cancer-cell Prot...mentioning
confidence: 99%
“…First, we confirmed that the ordinary larval behaviour observed on agarose substrates is maintained when using a collagen-treated microcavity as the substrate ( Supplementary Figure S3 ). We then used WARP (Meek et al, 2021) to enable imaging of substrate interactions at sufficiently high temporal resolution (for details of WARP analysis, see Supplementary Figure S4) . First, we examined protopodial indentations during forward peristaltic waves.…”
Section: Resultsmentioning
confidence: 99%
“…See Supporting Information Fig. S4 and (Meek et al, 2021) for further details on the calculation of displacement from the λ and λ θ images. All WARP and ERISM images were acquired using an Andor Zyla 4.2 sCMOS camera (Andor Technology, Belfast, UK).…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation